Postoperative intussusception following transverse colostomy: A case report with its pathogenesis - Shakya, VC; Agrawal, CS; Koirala, R; Khaniya, S; Shrestha, AB; Adhikary, S (Kathmandu University Medical Journal, 2010)
Postoperative idiopathic intussusception is considered to be a distinct entity, and has been reported following different operations. We present a 45-year-old female with postoperative ileoileal intussusception following a transverse loop colostomy for sigmoid volvulus, in which there was a kinked loop of bowel forming the lead point. The pathogenesis and literature review of this disorder is discussed. Key words: postoperative intussusception; lead point; kink; motility disorder DOI: 10.3126/kumj.v7i4.2769 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 429-431